2021
DOI: 10.1097/tgr.0000000000000331
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Myofascial Trigger Points in the First Dorsal Interosseous Muscle in Patients With Thumb Carpometacarpal Osteoarthritis Compared to Healthy Controls

Abstract: The author contributions are as follows: P.P.: Design of the study, data collection, tracking and interpretation of the results, and writing, submitting, and tracking the manuscript. M.P.L-R: Data collection and interpretation of the results, and writing, submitting, and tracking the manuscript. P.H.: Tracking and interpretation of the results, and writing, submitting, and tracking the manuscript. R.C-T: Tracking and interpretation of the results, and writing and tracking the manuscript. K.V: Design of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Notably, no latent nor active MTrPs were observed in 45 age-matched healthy asymptomatic individuals 41. However, Pedersini et al42 observed that the thumb carpometacarpal OA group demonstrated a 40% greater presence of either active or latent MTrPs in the first dorsal interosseous muscle compared with the asymptomatic controls (88% vs. 48%, respectively).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Notably, no latent nor active MTrPs were observed in 45 age-matched healthy asymptomatic individuals 41. However, Pedersini et al42 observed that the thumb carpometacarpal OA group demonstrated a 40% greater presence of either active or latent MTrPs in the first dorsal interosseous muscle compared with the asymptomatic controls (88% vs. 48%, respectively).…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, the findings of latent and active MTrPs only in the spine OA may somehow be associated with neck spine OA. Pedersini et al42 did not report whether MTrPs was latent or active in individuals with thumb carpometacarpal OA. Therefore, a better description of MTrPs in thumb carpometacarpal OA individuals is suggested to estimate its prevalence in thumb carpometacarpal OA individuals.…”
Section: Discussionmentioning
confidence: 98%
“…2,3 Among these instruments, the Visual Analog Scale (VAS) stands out as a widely validated and highly reliable tool that empower individuals to accurately self-report of their pain intensity. 4,5 It is acknowledged that perceived pain intensity is influenced by various factors, encompassing both individual pain thresholds and tolerances, as well as variables such as the type of injury, age, ethnicity, and anxiety. [6][7][8] These elements contribute to the complexity of pain assessment, which in turn can pose challenges for the health care professionals in the effective management of pain, potentially resulting in suboptimal treatment.…”
Section: Implications For Rehabilitationmentioning
confidence: 99%
“…Given the inherent subjectivity of pain, various methods and scales have been developed to quantify pain intensity and evaluate responses to therapeutic interventions 2,3. Among these instruments, the Visual Analog Scale (VAS) stands out as a widely validated and highly reliable tool that empower individuals to accurately self-report of their pain intensity 4,5…”
mentioning
confidence: 99%
“…The increasing aging population has created a demand for e-health technologies that support healthy aging, reduce health care costs, and address the limited availability of health care professionals. 1,2 These technologies encompass various information and communication technologies used in health care settings, including remote monitoring technologies (RMTs). [3][4][5] RMTs allow for the remote monitoring of individuals' health and the transmission of data to health care providers for review.…”
mentioning
confidence: 99%